Use of Rendered Terrestrial Animal By-products in Aquatic Feeds - Forster, Ian; Dominy, Warren (Avances en Nutrición Acuicola, 2019)
The demand for high quality, palatable protein ingredients for aquatic feeds has grown along with the aquaculture industry. Although fishmeal continues to play a significant role, its generally high cost, variability of supply and limited scope for increased fishmeal production have led to interest in identification and development of alternative protein sources. Rendered animal by-products are produced in significant quantities and are available in a variety of forms, including meat and bone meals and poultry by-product meals. A number of studies have shown that many of these by-products are suitable for inclusion in aquatic feeds in partial replacement of fishmeal. This paper reviews some of this research, with an emphasis on shrimp feeds. In general, rendered animal by-products can replace from 15 to 75% of fishmeal in diets for shrimp. Most of the published research on by-products was conducted in clean, flow-through water conditions, whereas shrimp are commercially cultured in outdoor ponds, where there is considerable opportunity for shrimp to supplement their diet with endogenous organic material (floc) from the culture environment. Under conditions of high floc availability, it has been found that rendered animal by-products may replace a significantly higher portion of fishmeal in diets for shrimp, without significant reduction of growth. Variability of the composition of the rendered material in by-products necessitates the profiling of incoming by-products before formulating to effectively use this material to meet the nutrient requirements of fish or shrimp.